2022
DOI: 10.1186/s12909-022-03353-3
|View full text |Cite
|
Sign up to set email alerts
|

Face-to-face versus distance learning of basic suturing skills in novice learners: a quantitative prospective randomized trial

Abstract: Background and aim Traditionally, practical skills are taught on face-to-face (F-F) basis. COVID-19 pandemic brought distance learning (DL) to the spotlight because of the social distancing mandates. We sought to determine the acceptability and effectiveness of DL of basic suturing in novice learners. Methods A prospective randomized controlled trial involving 118 students was conducted. Participants were randomized into two groups for learning sim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 60 publications
(107 reference statements)
1
3
0
Order By: Relevance
“…It was also found that online education can effectively complement the medical teaching process [47] and is useful in saving time and creating a flexible learning environment [48,49]. It was proved that even teaching surgical skills remotely is as effective and efficient as traditional medical education [50]. The results of these studies correspond with the data obtained from medical students examined in our study during the COVID-19 pandemic lockdown period (n = 111).…”
Section: Discussionsupporting
confidence: 82%
“…It was also found that online education can effectively complement the medical teaching process [47] and is useful in saving time and creating a flexible learning environment [48,49]. It was proved that even teaching surgical skills remotely is as effective and efficient as traditional medical education [50]. The results of these studies correspond with the data obtained from medical students examined in our study during the COVID-19 pandemic lockdown period (n = 111).…”
Section: Discussionsupporting
confidence: 82%
“…Unlike previously published studies, the digital platform and teaching methodology implemented in this study allowed time flexibility for both trainers and trainees. First, it allowed trainers to assess videos and provide individualized feedback at any time and from anywhere in the world, without the need to find available time away from clinical labor to teach the trainee [ 25 27 , 29 , 30 ]. Second, it provided the trainee the chance to train from any place they want and as many times as they feel comfortable while having unlimited access to the video-enhanced feedback received.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, previous studies also found that the level of satisfaction was higher in face-to-face vs. non-face-to-face teaching. Results from prior research carried out in the post COVID-19 era on healthcare degrees including nursing, physiotherapy, medicine or dentistry have shown the positive impact on face-to-face training in terms of social performance, knowledge integration, self-motivation, security and satisfaction [19][20][21][22][23]. These studies have been conducted in diverse settings that require both a strong practical component, such as suturing, anatomy or dissection, and a strong social interaction component, such as learning specific terminology for health professionals.…”
Section: Discussionmentioning
confidence: 99%